I NUNC-ES: strumenti nuovi per la linguistica dei corpora in spagnolo - Barbera, Manuel (Cuadernos de Filología Italiana, 2007)
After a short presentation of NUNC, a freely available multilingual suite of corpora based on newsgroups texts (querable online at http://www.bmanuel.org/projects/ng-HOME.html), this paper intends to investigate the Spanish subset of data collected in NUNC-ES. A brief description of the Spanish hierarchies is given, and some examples of corpus queries are suggested. The third part of the work presents an outline of future developments, especially the release of a new tagset for Spanish.